New Regulations for Foods Offered to School Children in Chile: Barriers to Implementation - Prochownik, Katherine; Vera Vergara, Mariana; J.Cheskin, Lawrence (International Journal of Nutrition, 2015)
Objective: To prevent childhood obesity, the Chilean government has recently implemented food regulation laws that apply to schools. This paper reviews the literature regarding the challenges in successfully integrating policies to regulate foods offered in schools. In addition, to understand some of the potential implementation barriers, a survey was conducted to evaluate how well food regulation laws were understood and implemented in Chilean schools. Methodology: A narrative literature review was conducted regarding food regulation policies in Chilean schools and potential barriers to implementation. This informed a subsequent descriptive, qualitative survey which was conducted in the Valparaíso region of Chile to examine knowledge, practices, and potential barriers to implementation of the new regulations. Twelve randomly-selected school food kiosk owners completed a survey and structured interview. Visual observations were also performed at each food kiosk. Content analysis identified trends in food items sold and determined the depth of understanding kiosk owners have of a specific new food law, "La Composición Nutricional de los Alimentos y Su Publicidad (20.606)." Key Results: 7 articles in Spanish and 10 in English were reviewed. The literature review revealed that unhealthful food options are readily available to Chilean students in school kiosks. The results of the survey and interview indicated that the school kiosk owners surveyed have a general understanding of the food law. 10 out of 12, however, were unsure of the law's exact contents. Unhealthful food options, inconsistent with regulation 20.606 were observed in all 12 visited kiosks. Conclusion: Evidence from a literature review and the survey findings confirm that unhealthful foods persist in Chilean schools, despite government food regulations. Although the majority of the school kiosk owners acknowledge law 20.606, most lack an understanding of its exact contents and their role in promoting healthier foods in schools. Further education of vendors and school administrators is needed to enhance compliance with the new Chilean food regulations.
Keywords: Food Regulation; Childhood Obesity; Chile; Schools; Implementation Barriers